THE HISTORY OF THE TASHKENT REGIONAL FINANCE DEPARTMENT IN ARCHIVE DOCUMENTS (1946-1955) - Ergashev Umid Mukhammed o‘g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article provides a description of the documents contained in Fund R-93, which is one of the key sources for studying the history of the Tashkent Regional Finance Department and is preserved in the National Archival Fund of Uzbekistan. Additionally, the issues that require attention in these documents have been comparatively analyzed based on information provided in other archival materials. In particular, the article presents data on the amount of revenue received by the regional local budget in 1950, as well as the amount of expenditures made from the regional local budget in the same year. Furthermore, based on the documents from Fund R-93, special attention has been given to the issue of personnel working in the Tashkent Regional Finance Department, and their ethnic background has also been analyzed using these archival records.